2014
DOI: 10.1007/s10900-014-9837-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices of Healthcare Workers in Relation to Bloodborne Pathogens in a Tertiary Care Hospital, Western Saudi Arabia

Abstract: To assess knowledge and practices of healthcare workers (HCWs) in relation to bloodborne pathogens in a tertiary care hospital, western Saudi Arabia. Self-administered questionnaire was distributed assessing demographic characteristics, knowledge and practices of physicians, nurses and technicians on risks of exposure and prophylaxis against human immunodeficiency virus, hepatitis B virus and hepatitis C virus infections. A total of 466 participants (151; 32.4 % physicians and 315; 67.6 % nurses/technicians) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…[2] However, surgeons do not seem to realize that as it has been clearly proven by this study and previous other studies which revealed low adherence to CDC standard precaution guidelines. [13,15,18,[24][25][26][27] HBV vaccine is necessary for HCWs, especially surgeons. [2] Other studies have found low HBV vaccination status among surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] However, surgeons do not seem to realize that as it has been clearly proven by this study and previous other studies which revealed low adherence to CDC standard precaution guidelines. [13,15,18,[24][25][26][27] HBV vaccine is necessary for HCWs, especially surgeons. [2] Other studies have found low HBV vaccination status among surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…[8,11,14,21] All these studies suggest that there were varying degrees of noncompliance to practice the standard precautions to prevent blood-borne pathogen transmission. [15,17,18,[24][25][26][27] Although surgeons perform high-risk procedures and are at high risk of acquiring blood-borne pathogens, only insignificant number of surgeons in different specialties practice the recommended prevention strategies such as wearing DG. [15,18,[25][26][27] Therefore, in this study, we assessed the surgeons' concerns and awareness of the practices of standard precautions in different surgical specialties in all surgical positions, with focus on highlighting possible gender differences.…”
mentioning
confidence: 99%